Contraceptive practice in Quirino province, Philippines: Experiences of side effects - Henry, Rebecca (DHS Qualitative Research Studies No. 1, 2001)
This study examined the contraceptive practices and the experiences of women in Quirino province of the Philippines in their use of contraceptives. Through semi- structured interviews with 81 married women and 20 health service providers, and observations of nurse/client interactions, field workers collected data on the use and understanding of family planning methods. The study found that some women use contraceptives in ways for which they were not designed, and that women stopped using a contraceptive method if they found that it did not "fit" with them, often because of its effect on menstruation.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
This report is one of five further analysis projects undertaken as part of the follow-up to the 1998 Philippines National Demographic and Health Survey (NDHS). Macro International Inc. coordinated the project and provided technical assistance. Funding was provided by the U.S. Agency for International Development (USAID). The NDHS further analysis project is part of the MEASURE DHS+ program which is designed to collect, analyze, and disseminate data on fertility, family planning, and maternal and child health. Additional information about the MEASURE DHS+ program may be obtained by writing to: MEASURE DHS+, Macro International Inc. 11785 Beltsville Drive, Suite 300, Calverton, MD, 20705 USA; Telephone: 301-572- 0200; Fax: 301-572-0999; E-mail: reports@macromt.com; Internet: www.measuredhs.com